Determinants of Immigrant Selectivity and Skills - Madeline Zavodny (Federal Reserve Bank of Atlanta, 2000)
Whether immigrants are positively or negatively self-selected is much disputed. Whereas most previous studies have addressed this question by comparing the wages of immigrants to those of U.S. natives, this analysis uses occupation to examine the skill level of immigrants. Data on the occupational distribution of individuals granted legal permanent residence in 1995 indicate that the proportion of immigrants in skilled occupations is related to the corresponding proportion in source countries but not necessarily to the return to skill and other economic factors in the country of origin.
Keywords: 330; Emigration and immigration; Labor mobility